Philosophy and literature at the Centenario: roads with reverse direction (Andamios, Revista de Investigación Social, 2015)
At the time of the Centenary, José Ingenieros became interested in philosophy and the value of philosophy as a builder of argentine culture. Is a time traversed by the nationalist discourse in the literature and by its pretensions to dominate the political space through cultural predominance. In this paper we analyze a central Ingeniero’s work on philosophy, Las direcciones filosóficas de la cultura argentina, trying to recognize there the dialog with Blasón de Plata, of Ricardo Rojas, and, indirectly, a response to literary nationalism. According to this interpretation, that dialog express the controversial nature of the “lettered city”, the fight for inhabiting it, for directing it, at the very time in which, according to Ángel Rama, it triumphed.
Keywords: José Ingenieros; Ricardo Rojas; philosophy; literature; national culture